An annotated Checklist of the Italian Butterflies and Skippers (Papilionoidea, Hesperiioidea) - Balletto, Emilio; Cassulo, Luigi A.; Bonelli, Simona (Zootaxa, 2014)
We present here an updated checklist of the Italian butterflies (Lepidoptera: Hesperioidea and Papilionoidea) organised in the following sections (tables): 1. Introduction, providing a broad outline of the paper. 2. Checklist proper, summarised in a table, listing, in separate columns: a. Indications of endemicity (sub-endemic, Italian endemic). b. The relevant Annex in the Habitats Directive (legally protected species). c. Threat levels (in Europe: for threatened species only). d. A serial number (whose format is uniform across all Italian animal groups). This number runs throughout all the following tables (see 3, 4). e. Name, author, date of publication. f. Schematic overall indication of each specie’s Italian range (N[orth], S[outh], Si[icily], Sa[rdinia]). 3. Nomenclature, containing basic nomenclatural details for all listed genera, species and some of the generally or historically recognised subspecies and synonyms. 4. Notes, where a variety of other information is provided, on a name by name (family, subfamily, genus, species, subspecies) basis. All remaining doubts as concerns each individual case are clearly stated. The number of nominal species listed in the previous edition of this checklist, published almost 20 years ago, was 275, whereas it has raised to 290 in the current list. The status of about a dozen of these remains controversial, as discussed in the text. The present checklist is meant to provide an update of the Italian butterfly fauna, taking into account all relevant publications, and tries to explain all nomenclatural changes that had to be introduced, in the appropriate section. Many detailed comments are offered, when necessary or useful, in the notes.